KINERJA TEKNOLOGI MESIN PENGOLAHAN SAGU SKALA KECIL DI KABUPATEN SUPIORI, PROVINSI PAPUA - Darma -; Budi Santoso; Reniana -; Moh Arif Arbianto (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Performance of Small-Scale Sago Processing Machinery in Supiori Regency, Papua Province. Papua is one of the largest sago producing regions in Indonesia with a potential sago area of 4.7 million ha. The production and utilization of sago starch in Papua is still very low compared to its potential, so that millions of tons of starch in sago stems have not been used. Increasing sago starch production can be done by transforming traditional processing methods to mechanical processing methods at the farm level. The objective of this study was to identify the utilization of small-scale sago processing machinery innovation in Supiori District, Papua Province. In this research it was applied small-scale sago starch processing machine consisting of sago rasping machine and starch extraction machine, both made by agroindustry workshop of Agricultural Technology Faculty, Papua University. Study results showed that application of the processing machinery was able to increase processing capacity 6 times higher than traditional method. The processing capacity was one trunk per day or equivalent to starch production 324 kg of wet sago starch per day. The machines worked properly with high performace. The performance of the machines applied were (a) rasping capacity 1,065 kg/hour, (b) extraction capacity 561.24 kg/hour, (c) starch percentage 39.16 % (d) starch loss in waste 1.80 % as well as (e) fuel consumption 1.46 litre/hour and 0.95 litre per hour for rasping machine and extraction machine respectively.Keywords: sagu, processing, machinery, small scale, technology performanceABSTRAK Papua merupakan salah satu daerah penghasil sagu terbesar di Indonesia dengan potensi areal sagu mencapai 4,7 juta ha. Produksi dan pemanfaatan pati sagu di Papua masih sangat rendah dibandingkan dengan potensinya, sehingga banyak jutaan ton pati dalam batang sagu belum digunakan. Peningkatan produksi pati sagu dapat dilakukan dengan mengubah metode pengolahan tradisional ke metode pengolahan secara mekanis di tingkat petani. Penelitian bertujuan mengidentifikasi pemanfaatan inovasi mesin pengolahan sagu skala kecil di petani Kabupaten Supiori, Provinsi Papua.  Pada penelitian ini telah diaplikasikan mesin pengolahan sagu skala kecil terdiri dari mesin pemarut sagu dan mesin ekstraksi pati sagu hasil produksi bengkel permesinan agroindustri, Fakultas Teknologi Pertanian, Universitas Papua. Hasil penelitian menunjukkan bahwa aplikasi mesin pengolahan skala kecil yang digunakan dapat meningkatkan kapasitas pengolahan 6 kali lipat dibandingkan dengan metode pengolahan tradisional. Kapasitas pengolahan adalah 1 pohon per hari atau setara dengan produksi pati basah 324 kg per hari.  Mesin yang diaplikasikan berfungsi baik dengan kinerja tinggi. Kinerja tersebut ditunjukkan oleh hal-hal berikut (a) Kapasitas pemarutan 1.065 kg/jam, (b) Kapasitas ekstraksi 561,24 kg/jam, (c) Rendemen pati basah 39,16 % (d) Persentase kehilangan pati terikut ke ampas 1,80 % dan (e) Konsumsi bahan bakar untuk mesin pemarut 1,46 liter/jam dan mesin ekstraksi 0,95 liter/jam.Kata kunci: sagu, pengolahan, mesin, skala kecil, kinerja teknologi